PERAN KOMUNIKASI PUBLIK DALAM PELAYANAN BANTUAN SOSIAL PADA BAGIAN KESEJAHTERAAN RAKYAT SEKRETARIAT DAERAH KABUPATEN BONE BOLANGO - Sri Handayani Suprapto (Universitas Muhammadiyah Gorontalo, 2015)
The aim of this research was to know how the role of public communication in service of social aid in part of secretariat public welfare Bone Bolango regency and how the feedback of public about Service of social aid in part of Secretariat Public Welfare Bone Bolango regency. Type of this research is qualitative descriptive with using 15 people as a sampling with doing the structured interview and described through the interviews. The results of this research say that the public communication that conducted in accordance with what is expected by the public because of the persuasive approach and with look the manners, politeness and even with a language that is easily understood by public it self. And communication by officials to the public in this case of compliance service of social aid is quite satisfactory even though there are things that not communicative even unwanted by the public, including many talk about the rules, change-unlike the procedures that had been said before, even so unfortunate when doing the Service of social aid there has unscrupulous officials that only it’s priority services to certain people who they know.